Studying the effectiveness of Group Therapy Based Life Enrichment and Enhancement Program on improvement of Therapeutic Indicates of Addiction in Dependent Men to Opiate - Kazemeini, Toktam; Abdekhodaei, mohammad saeid (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Despite significant advances in the field of detoxification and maintenance treatment, findings imply high rates of treatment failure and increase in the relapse even with the early success in detoxification. The purpose of this study was to examine the effectiveness of group therapy based life enrichment and enhancement program on improving of therapeutic indices of addiction in dependent men to opium. Material and methods: A quasi-experimental pretest-posttest design was used.The sample of the study consisted of 24 male substance abusers who were receiving methadone treatment in Iran Pak clinic , in Mashhad city. They were selected by convince method and randomly assigned in two experimental and control groups. Participants of experimental group attended in life enrichment and enhancement program for 5 sessions. Data were collected by 3 instruments : Personal Concerns Inventory, The Satisfaction with Life Scale and Craving and Temptation Scale which were completed by both groups before and after intervention. Data were analyzed by SPSS-18. Finding: Findings showed that the life enrichment and enhancement program significantly improved adaptive motivational structure score (P<0.01) and life satisfaction score (p<0.05) in intervention group. The LEEP also significantly decreased the craving and temptation scores in intervention group (P<0.05). Conclusion: Group therapy based Life enrichment and enhancement program can be an effective method in promotion of motivational structure, satisfaction with life and also reduction of temptation of drug abuse in men substance abusers who are under methadone treatment. Key words: Life Enrichment and Enhancement Program, Group therapy, Addiction, Opiate, The Satisfaction with Life, Temptation. REFERENCES Abdolhoseini, F (2009) [Comparative Study of Life Enhancement and Advancement Programme (LEAP) and REBT on Improving the Therapeutic Indices of Female Drug Abusers] (Dissertation). Mashhad: Ferdowsi University of Mashhad. (Persian) Bahrami E (2011) [Addiction and Prevention Process]. Tehran: The Organization for Researching and Composing University Textbooks in the Humanities (Samt). (Persian) Bayani. A A, Mohammad Koocheky A, Goodarzi H (2007) [The reliability and validity of the satisfaction with life scale]. Journal of Iranian Psychologists . 3(11) 259-265. (Persian) Cox W M and Klinger E (1988) A motivational model of alcohol use. Journal of Abnormal Psychology . 97(2) 168-80. Cox W M and Klinger E (2002) Motivational structure: Relationships with substance use and processes of change. Addictive Behaviors . 27(6) 925-940. Diener E, et al (1985) The Satisfaction with Life Scale. Journal of Personality Assessment . 49 (1)71-75. Fadardi J S (2003) Motivational and Cognitive Determinants of Attentional Bias for Alcohol-Related Stimuli: Implications for a New Attentional-training . (Dissertation). Bangor: University of Wales. Fadardi J S and Cox W M (2008) Alcohol-attentional bias and motivational structure as independent predictors of social drinkers alcohol consumption. Draug and Alcohol Dependence . 97(3) 247-256. Fadardi J S, Cox W M and Klinger E (2006) Life Enrichment and Advancement Program (Leap): A self- Help Manual for Reducing Your Need to Drink . University of wales, Bangor,Uk. 85 150-155. Fadardi J S, Ziaee S S and Barerfan Z (2008). [The Persian Post-Detoxification Craving and Temptation Scale]. Mashhad:Unpublished Manual. Faul F, et al., (2007) G*Power 3: A flexible statistical power analysis program for the social behavioral and biomedical sciences. Behavior Research Methods . 39 (2)175-191. Fleming M F, Barry K L (1998). Addictive Disorders . Mosby Year Book. Goodarzi N, et al (2008) [The effectiveness of group contracting and behavioural activation therapy on opioid substance use disorders]. Contemporary Psychology 3(1) 3-13. (Persian) Mohammadi M, Dahganpoor M (2004) [Psychopathology of substance abuse]. National Institute of Drug Studies: Ayene book. (Persian) Mozaffari S H (2003) [Personality correlates of subjective happiness among students of Shiraz University based on The five factor model]. (Dissertation). Shiraz: Shiraz University. (Persian) Raadi M, Rezaie R (2001) [prevention of addiction special for families, Preventive cultural Administration of kurdestan rehabilitation org]. (Persian) Rahimi M M K, Mohammad K, Razaghi E M (2002) [The 30- year- old process of drug usage in Iran]. Hakim Research Journal . 5 (3) 171-182. (Persian) Shamloo Z S and Cox W M (2009) The relationship between motivational structure, sense of control, intrinsic motivation and university students’ alcohol consumption. َive Behaviorss. 35(2) 140-146. Ziaee S S (2009) [Effect of attention control training on the reduction of attentional bias in drug abusers]. (Dissertation). Mashhad: Ferdowsi University of Mashhad. (Persian)